Novorojenec z nižjo porodno težo kot medicinski in družbeni problem - Burja, Silva (Obzornik zdravstvene nege, 1978)
According to available studies, 10-15 % of inlants are bom under circumstances which lessen their chance to survive. The data revealing a 50-per cent neonatal mortality within the first day of life stress the need for adequate measures to be undertaken in due time. The author presents the organization of the health service and reviews the investigations and analyses carried out by our own and other experts in this field. Finally, the measures are presented which should be undertaken, not only to lower the perinatal death rates, but also to prevent the invalidity of children, which have both assumed great medico-social significance.